2017
DOI: 10.1007/s00414-017-1715-2
|View full text |Cite
|
Sign up to set email alerts
|

How taphonomic alteration affects the detection and imaging of striations in stab wounds

Abstract: Stabbing with a kitchen knife is a common method of homicide in Europe. Serrated knives may leave tool markings (striations) in tissues. Documentation of striations is necessary for their use as forensic evidence. Traditional methods (physical casting and photography) have significant limitations, and micro-computed tomography (micro-CT) has been trialled in cartilage to Bvirtually cast^wounds. Previous research has shown the proportion of striations in cartilage falls following decomposition. This project has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Afterward, several experimental studies have demonstrated that micro-CT is useful to document the morphology (i.e., shape, walls, floor, angles) of stab wounds on cartilage and bones (i.e., without maceration) being even more accurate than macrophotography and scanning electron microscopy [30]. A proposed qualitative tool mark classification allowed the distinction between the weapon causing the injury (i.e., hatchet, knife) as well as the estimation of the trajectory used at tool impact [31,32].…”
Section: Tool Markmentioning
confidence: 99%
“…Afterward, several experimental studies have demonstrated that micro-CT is useful to document the morphology (i.e., shape, walls, floor, angles) of stab wounds on cartilage and bones (i.e., without maceration) being even more accurate than macrophotography and scanning electron microscopy [30]. A proposed qualitative tool mark classification allowed the distinction between the weapon causing the injury (i.e., hatchet, knife) as well as the estimation of the trajectory used at tool impact [31,32].…”
Section: Tool Markmentioning
confidence: 99%
“…Several articles describe exposure effects on invasive marks, such as exposure to heat [ [144] , [145] , [146] ] or taphonomic alterations [ 147 ]. Macoveciuc et al.…”
Section: Invasive Striated and Impression Toolmarksmentioning
confidence: 99%
“…Stanley et al. [ 147 ] describe the effect of taphonomic alterations on striations in skin (porcine). They see a big effect and recommend to document skin striations as soon as possible by stereo-optical microscopy.…”
Section: Invasive Striated and Impression Toolmarksmentioning
confidence: 99%
“…The primary goals of embalming are sanitization, presentation, preservation, and restoration [2]. Accident victims, stab wounds, dissected bodies or anything that mutilates the body structure have been reported to influence decomposition process [3][4][5]. Therefore, embalming decomposing bodies resulting from stab wounds require specialist attention [6].…”
Section: Introductionmentioning
confidence: 99%